Sounding Off Rhythm, Music, and Identity in West African and Caribbean Francophone Novels - Huntington, Julie (African Soundscapes, 2009)
Intrigued by "texted" sonorities-the rhythms, musics, ordinary noises, and sounds of language in narratives-Julie Huntington examines the soundscapes in contemporary Francophone novels such as Ousmane Sembene's God's Bits of Wood (Senegal), and Patrick Chamoiseau's Solibo Magnificent (Martinique). Through an ethnomusicological perspective, Huntington argues in Sounding Off that the range of sounds -footsteps, heartbeats, drumbeats-represented in West African and Caribbean works provides a rhythmic polyphony that creates spaces for configuring social and cultural identities. Huntington's analysis shows how these writers and others challenge the aesthetic and political conventions that privilege written texts over orality and invite readers-listeners to participate in critical dialogues-to sound off, as it were, in local and global communities.